Energy efficiency in buildings / Tengku Mohd Zainudin Tengku Hanafi - Tengku Hanafi, Tengku Mohd Zainudin (Faculty of Mechanical Engineering, 1995)
The purpose of this final project is to study the method of planning, reporting, costing, auditing, application and implementation of energy to achieve its efficient use. This project describe the demand side of energy efficiency of energy usage which is .cost reduction on the Central Unit Air Conditioning System ( usually the highest electricity consumption in buildings). This project can also help to guide Engineers and those who involve in engineering fields of how energy efficiency can be applied and consequently to the property and account department of the organization. Good housekeeping can provide significant savings with little or no investment at all.